Meta-Nudging Honesty: Past, Present, and Future of the Research Frontier - Eugen Dimant; Shaul Shalvi (Center for Economic Studies and ifo Institute (CESifo), 2022)
Achieving successful and long-lasting behavior change via nudging comes with challenges. This is particularly true when choice architects attempt to change behavior that is collectively harmful but individually beneficial, such as dishonesty. Here, we introduce the concept of 'meta-nudging' and illustrate its potential benefits in the context of promoting honesty. The meta-nudging approach implies that instead of nudging end-users directly, one would nudge them indirectly via "social influencers". That is, one can arguably achieve better success by changing the behavior of those who have the ability to enforce other's behavior and norm adherence. We argue that this represents a promising new behavior change approach that helps overcome some of the challenges that the classical nudging approach has faced. We use the case of nudging honesty to develop the theoretical foundation of meta-nudging and discuss avenues for future work.
Keywords: C91; D01; 330; behaviour change; honesty; lying; nudging